Sintesis dan Karakterisasi Biochar-Fe Nanoparticles dari Limbah Kulit Kopi - Riskal Fadli; Muhammad Damris; Ira Galih Prabasari (Jurnal Teknik Kimia USU, 2026)
Coffee husk waste has the potential to cause environmental problems if not properly managed. One promising utilization approach is its conversion into biochar. In this study, biochar was produced via pyrolysis at temperatures of 400 °C, 500 °C, and 600 °C. The final temperature was maintained for 1 hour, after which the material was synthesized using ferric chloride hexahydrate (FeCl₃·6H₂O) as an iron precursor through a base precipitation reaction in 1.5 M NaOH solution at 80 °C for 4 hours. SEM–EDX characterization results showed that increasing the pyrolysis temperature influenced pore structure development, where higher temperatures led to smaller pore diameters and denser surface morphology after Fe incorporation. The highest Fe content was obtained in biochar produced at 600 °C, reaching 14.32%. The utilization of coffee husk waste as a precursor for Fe-modified biochar demonstrates potential for enhancing Dissolved Organic Carbon stabilization. This potential is attributed to the material characteristics obtained, namely the combination of a porous structure and the presence of active iron phases, which theoretically can enhance chemical interactions and binding capacity toward dissolved organic compounds.